Direct Writing Unclonable Watermarks with an Electrochemical Jet. (4th October 2022) - Speidel, Alistair; Bisterov, Ivan; Clare, Adam Thomas
Abstract: Counterfeit parts result in significant losses per annum and are often dangerous, therefore they represent a serious concern for manufacturers and end users alike. Easily written but unclonable watermarks undermine the proposition of the counterfeiter. Here, a rapid electrochemical jet engraving routine is presented to encode robust materials with self‐organized dendritic structures at length scales that can be imaged with a smartphone. Surface defects act as stochastically distributed seeds from which discrete pitting events can be propagated by translating the electrochemical field. While the vascular pathways can be directly written at the macro scale, the formation and propagation of microscale dendritic arms is chaotic, caused by the implicit randomness of the defect seeds and the supply of ions to the surface. The latter is confounded by random perturbations in the flow condition. Each engraved dendrite is unique, stable at high temperature (>500 °C) and can be subjected to rapid image recognition to allow individual mark identification at any point during part production and delivery, or through part lifetime. Abstract : Unclonable vascular arrays are electrochemically engraved onto metallic engineering parts to create robust but unique tags to deter counterfeiting. These tags are easy to read and verify but are impossible to clone and therefore present an anticounterfeiting opportunity through production and through the lifetime of a part or consumer good.